POLITICAL AND PHILOSOPHICAL ANALYSIS OF THE CONCEPT AND MODEL OF MODERNIZATION - Bakhtiyor Omonov (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses classical, modern, non -traditional, traditional concepts of political modernization, analyzes the theory and practice of the transition from an agrarian society to industrial, and scientific conclusions were made.